The Effect of Peer Relation and Peer Pressure on the Performance of University Students: A Quantitative Study - Khan, Zainab; Athar, Shamaila; Mehmood, Umair; Khan , Waqas A. (Pakistan Journal of Humanities and Social Sciences, 2023)
Peer relations shows a pivotal role in the academic journey of university students, encompassing both supportive relations and the influence of peer pressure. This study delves into the connections among peer relations, peer pressure, and the academic achievements of university students. Its primary objective is to investigate the links between the quality of peer interactions and the degree of peer pressure with academic performance. This study adopts a quantitative research design, survey design with random sampling and tries to investigate how these peer-related characteristics affect students' performance. Random sampling will be utilised to pick a representative sample of 600 university students from diverse faculties and academic years. The research is based on data obtained, and the following significant conclusions were observed: the analysis of the data revealed a positive association between peer relations and peer pressure, showing that as peer relations improve, peer pressure tends to grow. Positive link is found in the study involving peer pressure and academic achievement, suggesting that students confronting complicated degrees of peer pressure tended to perform better academically. This conclusion urges additional inquiry into the mechanisms by which peer pressure can contribute to improved academic achievement. Positive social relations can be considered as a vital benefit for academic performance, while the function of peer pressure in determining academic outcomes is an exciting subject for further research. Understanding the complexities of peer interactions and their impact on academic performance is crucial for educators, politicians, and students alike. Further research is needed to delve deeper into the intricacies of these relationships and to explore potential interventions and strategies that can enhance the overall university experience for students.